Application of global mapping indices for change detection in coal mining areas of Salanpur block of Paschim Bardhaman district, West Bengal - Sangita Mahata; Vishwambhar Nath Sharma (National Geographical Journal of India, 2023)
The article is about the application of global mapping indices for detecting changes in vegetation cover, water bodies, bare soil, and built-up areas using the Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI), Normalized Difference Soil Index (NDSI), Normalized Difference Water Index (NDWI) and the Global Environment Monitoring Index (GEMI). In this study, Landsat remote sensing imagery was used to quantify change detection in coal mining areas of the Salanpur block. The aim was to analyze different land cover types using Landsat imagery with a twenty-year interval from 2001 to 2021. The mineral-bearing areas have been identified as one of the global sources of income but the research carried out from such resource-rich areas revealed that these areas experienced a rapid loss of vegetation cover and other environmental degradation due to the gigantic expansion of mining projects. These indices are used to extract information concerning land issues due to anthropogenic activities. The results obtained from these indices in this study show conversions of vegetation land when the land was put to some excavation activities or other developmental work. This study shows an effort to monitor major entities like water bodies, vegetation cover, bare ground, and urban areas. It also shows the suitability of these mapping indices for detecting changes concerning the mining environment.